Enhancing Population Administration Services: Assessing Community Satisfaction at Kios Pelanduk - Mali, Matheus Gratiano; Maulidyah, Dinda Aulia (Jurnal Borneo Administrator, 2025)
This study evaluates the service quality of Kios Pelanduk, a population administration innovation by Dispendukcapil Kebumen, focused on Jatiluhur and Jatipurus Villages. Employing qualitative methods and NVivo tools, the research examines community satisfaction based on the Community Satisfaction Index (IKM) and highlights perceptions of fast, easy, and reliable services. Key findings reveal high satisfaction levels due to clear requirements, efficient procedures, and competent operators. However, challenges persist, including infrastructure limitations, procedural delays, and uneven adoption across villages. Despite these challenges, the initiative demonstrates significant success in enhancing population administration services, with steady progress in document ownership and satisfaction indices. Recommendations include improving infrastructure, expanding adoption to remote areas, and addressing service delays to ensure broader and more effective implementation. This study underscores the potential of local-level innovations in advancing public service delivery and provides actionable insights for policymakers